Plant-based food and protein trend from a business perspective: markets, consumers, and the challenges and opportunities in the future - Aschemann-Witzel, Jessica; Gantriis, Rebecca Futtrup; Fraga, Paola; Perez-Cueto, Federico J. A. (Critical reviews in food science and nutrition, 2021)
The food sector is increasingly turning toward sustainability issues. A sustainable food system should provide sufficient, nutritious food for all within limited natural resources. Plant-based food and proteins are a recent, growing trend setting out to contribute to this challenge. However, food industry stakeholders need to be aware of the challenges and opportunities. This paper reviews the trend from a business perspective. It outlines the global drivers, market trends, market data observations, and consumer behavior factors of relevance, and pinpoints the strengths, weaknesses, opportunities and threats (SWOT) for food sector companies. Findings suggest that the policy and market context is favorable in the near future, but that consumer beliefs, perception and understanding has to change further for the business opportunity to grow on a larger scale. More innovations are needed, in particular in the direction of meat-replacements that are healthy as well as clean label.